INFORMATION TELECOMMUNICATIONS OF PUSHCHINO RADIO ASTRONOMY OBSERVATORY, ASTRO SPACE CENTER OF LEBEDEV PHYSICAL INSTITUTE - Dumsky, V.; Isaev, E. A.; Samodurov, V. A.; Likhachev, S. F.; Shatskaya, M. V.; Kitaeva, M. A.; Zaytcev, A. Yu.; Ovchinnikov, I. L.; Kornilov, V. v. (Одеські астрономічні публікації, 2013)
Buffer data center was created in the territory of the Pushchino Radio Astronomy Observatory three years ago. The necessity of its creation was caused by the high requirements to the speed and quality of the transmission large amounts of scientific and telemetry data received by tracking station RT-22 from the space radio telescope of the international project “Radioastron”. The transfer of this data is carried out over a long distance over100 kmfrom the Pushchino toMoscowcenter of processing and storage ASC FIAN. And now we use the data center as a center of local network of the Observatory.